Respons Pemupukan pada Model Biologi Pohon Pepaya California (Carica papaya L.) Fase Vegetatif - Idris, Idris Dwiky Cahyanto; Mei A, Silvia F (Program Studi Agroteknologi, 2023)
California papaya (Carica papaya L.) is one type of papaya that is very popular with many people because it tastes sweet and nutritious. The height of this papaya tree is somewhat dwarfed by 1.5-2 m with a short stem and midrib. This plant can bear heavy fruit up to 25-30 fruit, the application of a combination of phonska fertilizer, sp-36 and KCl on papaya plants seeks to increase productivity and growth in fruit, the average sweetness of papaya fruit reaches 10.1-12 Briks are very sweet and of course rich in protein. This research was conducted in Pancakarya Village, Ajung District, Jember Regency from December 2021 to March 2022. The study used a factorial pattern with a factorial randomized block design (RAK) with 3 x 3 repetitions with 3 replications. Factor I The branching biology model of the California papaya plant consists of: d1b1, d1b2, d1b3, d2b1, d2b2, d2b3, d3b1, d3b2, d3b3. With information (d) namely dose, (b) stem and interaction (db). The application of fertilizer once a week, a combination of phonska, sp-36 and KCl gave no significant effect on the observed parameters of plant height (cm), number of leaves (strands), canopy increase rate (cm), percentage of productive segments (%) but not with the observation that the percentage of normal fruit has a very different effect, in fact the application of a mixture of phonska, sp-36 and KCl fertilizers affects the sweetness level of california papaya fruit.